PERAN BAITUL MAAL WA TAMWIL (BMT) DALAM UPAYA PEMBERDAYAAN EKONOMI MASYARAKAT - Anam, Moh.; Mufida, Nur (AL-MANSYUR, 2024)
This research aims to find out whether Baitul Maal wa Tamwil (BMT) has an active and important role in the non-bank financial sector. The presence of Baitul Maal wa-Tamwil (BMT) in an area is based on the fact that it has not been "touched" and the reach of the lower strata of society (the poor) by banking financial institutions. The existence of BMT is a challenge for Muslims, especially for Muslim leaders and Sharia banking practitioners, to be able to demonstrate the quality and professionalism of BMT in meeting the aspirations and demands of the Ummah related to economic activities, so that BMT's success in realizing the demands of the Ummah will, in turn, position BMT as an Islamic financial institution that is capable and credible. For this reason, BMT's efforts and role in improving the economic position of the people must show its performance in its capacity as a financial institution that has the ability to play a role and as an alternative for the community in business cooperation and business partnerships. It has been proven that BMT has an active role in supporting government programs in reducing poverty, this can be seen from the vacancies created by BMT through the distribution of financing to the community in the form of UMKM.